Behavior of copper‐containing high‐entropy alloys in harsh metal‐dusting environments. Issue 7 (12th February 2021) - Galetz, Mathias C.; Schlereth, Clara; White, Emma M. H.
Abstract: Metal dusting is still an unresolved issue at high temperatures. Currently, two material‐related strategies to mitigate metal dusting are described in the literature. On the one hand, highly alloyed materials are used, which contain large amounts of protective oxide‐forming elements, such as Cr, Al, and Si. The second mitigation strategy is based on inhibiting the catalytic effect of Fe, Ni, and Co. These elements all strongly catalyze the formation of solid carbon from the gas phase. Combining the catalytic protection of Cu alloying for metal dusting with protection by a classical alumina/chromia barrier is a native feature that high‐entropy alloys (HEAs) can offer. In this study, the behavior of different equiatomic HEAs with and without Al and/or Cu are studied when exposed at 620°C in a highly aggressive metal‐dusting environment. Abstract : Combining the catalytic protection of Cu alloying for metal dusting with protection by a classical alumina/chromia barrier is a native feature that high‐entropy alloys (HEAs) can offer. In this study, the behavior of different equiatomic HEAs with and without Al and/or Cu are studied when exposed at 620°C in a highly aggressive metal‐dusting environment.